Multi-element co-doped sodium ion positive electrode material and its preparation method and use

Multi-element co-doped sodium ion cathode materials address the limitations of sodium ion batteries by enhancing structural stability and electrochemical performance, enabling high capacity retention and stability in sodium ion batteries.

JP2024546419AActive Publication Date: 2024-12-24SHANGHAI ENERGY NEW MATERIALS TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024527281
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-05-13
Filing Date
2022-06-23
Publication Date
2024-12-24
Estimated Expiration
2042-06-23

AI Technical Summary

Technical Problem

Lithium-ion batteries face challenges due to lithium resource depletion, high costs, and uneven global distribution, while sodium ion batteries suffer from low specific capacity, poor structural stability, and fast capacity decay, limiting their commercialization.

Method used

A multi-element co-doped sodium ion cathode material with a chemical formula NaαMbCucTiβO2+ε, where M is Ni, Co, Mn, Cr, V, Al, Fe, B, Si, or Zn, is prepared through high-temperature solid phase or coprecipitation methods, enhancing structural stability and electrochemical performance.

Benefits of technology

The multi-element co-doping improves the sodium ion cathode's structural stability and electrochemical performance, achieving high capacity retention and stability even after multiple charge/discharge cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024546419000001_ABST
    Figure 2024546419000001_ABST
Patent Text Reader

Abstract

The present invention provides a multi-element co-doped sodium ion cathode material, the cathode material being in the O3 phase, with a space group of R-3m, and its chemical formula is Na α M a Li b Cu c Ti d O 2+β wherein M is at least one of Ni, Co, Mn, Cr, V, Al, Fe, B, Si, Mg, and Zn, and 0.5≦α≦1, -0.1≦β≦0.1, 0
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of materials technology, and in particular to a multi-element co-doped sodium ion positive electrode material and its preparation method and use. [Background technology]

[0002] In recent years, lithium-ion batteries have grown explosively, and the demand for 3C, energy storage and power fields is increasing day by day. However, lithium-ion batteries face problems such as the depletion of lithium resources and nickel and cobalt ores, especially the price of lithium ore is rising year by year, and even if all the lithium resources explored in the world are mined, it is not enough to meet the explosively growing demand for lithium-ion batteries. In addition, the distribution of lithium resources is very uneven worldwide, and 80% of China's lithium ore needs to be imported from South America, which brings serious risks to national energy security. Therefore, we start to look for other alkali metal batteries with large resource abundance, wide distribution, low price and high electrochemical performance. In addition to having the above advantages, sodium-ion batteries are fully compatible with lithium-ion batteries, and most of the auxiliary materials and processes are the same or similar.

[0003] Sodium ion batteries are mainly composed of a positive electrode, a negative electrode, a separator electrolyte and other auxiliary materials. The performance of the positive electrode determines the performance of the battery. Common sodium ion positive electrode materials usually have disadvantages such as low specific capacity (less than 135 mAh / g), poor structural stability and air stability. The routes to obtain higher capacity mainly include expanding the voltage section, introducing active lattice oxygen, and doping electrochemically active elements (mainly increasing the Ni content). The former two tend to sacrifice the cycle life of the material and are difficult to achieve both structural stability and high capacity, and may cause a decrease in discharge pressure uniformity, while the latter significantly increases the cost of raw materials, which is contrary to the low-cost concept of sodium ion positive electrode materials. The most commonly used solution is to optimize the structure by doping, but the doping effect of a single element is always limited and cannot be improved in terms of structure and performance. That is, to obtain a long cycle life, the structure can be stabilized by doping with an element, but the doping of a single element cannot meet the design requirements of high capacity and long cycle.

[0004] Common sodium ion cathodes are mainly of three types: oxide, Prussian blue, and polyanion. Oxide has the advantages of high specific capacity, low cost, high voltage, wide source of raw materials, and environmental friendliness, and has gradually become a technical hotspot in academia and industry. However, oxide cathode materials face problems such as low structural stability due to phase change, fast capacity fade, and poor air stability, which slows down the progress of large-scale commercialization. Summary of the Invention

[0005] The objective of the present invention is to realize the synergistic effect of multiple elements through a multi-element co-doping method to achieve the objective of improving both the structure and electrochemical performance of the positive electrode material.

[0006] Therefore, the present invention provides a multi-element co-doped sodium ion cathode material, in which the cathode material is in the O3 phase, has a space group of R-3m, and has the chemical formula Na α M aLi b Cu c Ti d O 2+β wherein M is at least one of Ni, Co, Mn, Cr, V, Al, Fe, B, Si, Mg, and Zn, and 0.5 ≦ α ≦ 1, -0.1 ≦ β ≦ 0.1, 0 < a < 0.95, 0 < b < 0.25, 0 < c < 0.3, 0 < d < 0.6, a + b + c + d = 1, and it satisfies electrical neutrality. A sodium ion cathode material by multi - element co - doping is proposed.

[0007] Preferably, M is one, two, or three of Ni, Mn, and Fe.

[0008] Preferably, 0.05 ≦ a + b + c < 1.

[0009] The present invention also provides a method for preparing the sodium ion cathode material by multi - element co - doping. The method comprises weighing appropriate amounts of a Na - element - containing compound, an M - element - containing compound, a Li - element - containing compound, a Cu - element - containing compound, and a Ti - element - containing compound according to the atomic ratio of Na element, M element, Li element, Cu element, and Ti element in the chemical formula Na α M a Li b Cu c Ti d O 2+β mixing them to obtain a mixture, and firing the mixture to obtain a sodium ion cathode material by multi - element co - doping. A method for preparing the sodium ion cathode material by multi - element co - doping is proposed.

[0010] Preferably, the M - element - containing compound, the Li - element - containing compound, the Cu - element - containing compound, and the Ti - element - containing compound are independently at least one of metal oxides, metal nitrates, metal sulfates, metal carbonates, and metal chlorides.

[0011] Preferably, the Na - element - containing compound is at least one of sodium carbonate, sodium hydroxide, and sodium bicarbonate.

[0012] Preferably, the weighed amount of the Na element-containing compound is 100% to 110% of the theoretical amount calculated according to the atomic ratio of Na element, M element, Li element, Cu element, and Ti element.

[0013] Preferably, the weighed amount of the Na element-containing compound is 102% to 106% of the theoretical amount.

[0014] Preferably, the weighed amount of the Li element-containing compound is 100% to 110% of the theoretical amount.

[0015] Preferably, the weighed amount of the Li element-containing compound is 102% to 106% of the theoretical amount.

[0016] Preferably, the mixing step includes mixing a Na element-containing compound, an M element-containing compound, a Li element-containing compound, a Cu element-containing compound and a Ti element-containing compound, and mechanically milling the mixture to obtain a mixture.

[0017] Preferably, the mechanical milling speed is 100 rpm to 1000 rpm, and the time is 1 hour to 48 hours.

[0018] Preferably, the firing temperature is 700° C. to 1050° C., the firing time is 6 hours to 36 hours, and the heating rate is 1° C. / min to 20° C. / min.

[0019] The present invention also provides a method for preparing the above multi-element co-doped sodium ion positive electrode material, comprising the steps of: 3 or M(OH) 2 According to the atomic ratio of M element in the above, an appropriate amount of M element-containing nitrate or M element-containing sulfate is weighed out and dissolved in water, and the pH is adjusted with a precipitant and a complexing agent to uniformly precipitate the precursor MCO. 3 or M(OH) 2 and obtain the chemical formula Na α M a Li b Cu c Ti d O 2+βAccording to the atomic ratio of Na, M, Li, Cu, and Ti in the Na-containing compound, Li-containing compound, Cu-containing compound, Ti-containing compound, and precursor MCO 3 or M(OH) 2 and calcining the mixture to obtain a multi-element co-doped sodium ion positive electrode material.

[0020] Preferably, the Li element-containing compound, the Cu element-containing compound, and the Ti element-containing compound are independently at least one of a metal oxide, a metal nitrate, a metal sulfate, a metal carbonate, and a metal chloride.

[0021] Preferably, the Na element-containing compound is at least one of sodium carbonate, sodium hydroxide, and sodium hydrogen carbonate.

[0022] Preferably, the weighed amount of the Na element-containing compound is 100% to 110% of the theoretical amount calculated according to the atomic ratio of Na element, M element, Li element, Cu element, and Ti element.

[0023] Preferably, the weighed amount of the Na element-containing compound is 102% to 106% of the theoretical amount.

[0024] Preferably, the weighed amount of the Li element-containing compound is 100% to 110% of the theoretical amount.

[0025] Preferably, the weighed amount of the Li element-containing compound is 102% to 106% of the theoretical amount.

[0026] Preferably, the pH in the precursor obtaining step is 7.5 to 13, the precipitating agent is sodium hydroxide or sodium carbonate, the complexing agent is aqueous ammonia, the drying temperature is 80° C. to 150° C., and the drying time is 6 hours to 48 hours.

[0027] Preferably, the mixing step is performed by mixing a Na element-containing compound, a Li element-containing compound, a Cu element-containing compound, a Ti element-containing compound, and a precursor MCO. 3 or M(OH) 2 It involves mixing the compounds and mechanically milling them to obtain a mixture.

[0028] Preferably, the mechanical milling speed is 100 rpm to 1000 rpm, and the time is 1 hour to 48 hours.

[0029] Preferably, the firing temperature is 700° C. to 1050° C., the firing time is 6 hours to 36 hours, and the heating rate is 1° C. / min to 20° C. / min.

[0030] The present invention also provides a sodium ion battery comprising the above-mentioned multi-element co-doped sodium ion positive electrode material.

[0031] Preferably, the sodium ion battery is used in low speed two-wheelers, electric vehicles, wind power generation, peak regulating of smart grids, solar power generation, domestic power supply, or large scale energy storage devices of communication base stations.

[0032] According to the present invention, Li + Since Li has a larger ionic radius and stronger Li-O bond energy, the lattice oxygen can be activated at high voltages, and O 2- / O n- Realize reversible capacitance in the electric couple, Ti 4+ Ni 2+ / Ti 4+ -O 2- It can improve the covalent bond properties, make the structure more stable, reduce cation mixing, inhibit multi-phase transition, and stabilize the layered structure of the material. 2+ can obviously improve the air stability of the material, and Cu 2+ / Cu 3+ can also provide partial capacity, which provides the positive electrode material of the present invention with high structural stability and high electrochemical performance. [Brief description of the drawings]

[0033] [Figure 1] 1 is a SEM topography of Example 1. [Diagram 2] 1 is an SEM topography of Example 3. [Diagram 3] 1 shows XRD spectra of Examples 3 and 4. [Figure 4] FIG. 1 is a graph showing the electrochemical performance in the first cycle of Examples 4 and 5. [Diagram 5] FIG. 1 is a performance chart of the first 100 cycles of Example 1, Example 4, and Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0034] Hereinafter, specific embodiments of the present invention will be described in detail with reference to the drawings. It should be understood that the specific embodiments described herein are merely for the purpose of explaining and interpreting the present invention, and are not intended to limit the present invention.

[0035] The endpoints of any ranges and any values ​​disclosed herein are not limited to the exact ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. Numerical ranges between the individual range endpoints, between the individual range endpoints and any single point value, and between any single point value can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be considered to be specifically disclosed herein.

[0036] The first embodiment of the present invention is a multi-element co-doped sodium ion cathode material, which is in the O3 phase, has a space group of R-3m and has the chemical formula Na α M a Li b Cu c Ti d O 2+βA multi-element co-doped sodium ion cathode material that satisfies electrical neutrality is proposed. In the formula, M is at least one of Ni, Co, Mn, Cr, V, Al, Fe, B, Si, Mg, Zn. Specifically, it may be one, two, or three of Ni, Mn, Fe, but is not limited thereto. α is the number of Na element atoms per cathode material, and 0.5 ≤ α ≤ 1. 2 + β is the number of O element atoms per cathode material, and -0.1 ≤ β ≤ 0.1. a is the number of M element atoms per cathode material, and 0 < a < 0.95. b is the number of Li element atoms per cathode material, and 0 < b < 0.25. c is the number of Cu element atoms per cathode material, and 0 < c < 0.3. d is the number of Ti element atoms per cathode material, and 0 < d < 0.6. And a + b + c + d = 1. Also, a + b + c can satisfy the condition of 0.05 ≤ a + b + c < 1, but is not limited thereto.

[0037] The second embodiment of the present invention proposes a method for preparing a multi-element co-doped sodium ion cathode material. The multi-element co-doped sodium ion cathode material is as described above, and the description thereof is omitted here. This method is a high-temperature solid-phase method, and the detailed steps are as follows: First, the chemical formula Na α M a Li b Cu c Ti d O 2+βThe mixture is obtained by weighing out appropriate amounts of a Na element-containing compound, an M element-containing compound, a Li element-containing compound, a Cu element-containing compound, and a Ti element-containing compound according to the atomic ratio of the Na element, the M element, the Li element, the Cu element, and the Ti element in the above. Specifically, the M element-containing compound, the Li element-containing compound, the Cu element-containing compound, and the Ti element-containing compound may be independently at least one of a metal oxide, a metal nitrate, a metal sulfate, a metal carbonate, and a metal chloride, but is not limited thereto. For example, the M element-containing compound is at least one of an M element-containing oxide, an M element-containing nitrate, an M element-containing sulfate, an M element-containing carbonate, and an M element-containing chloride, the Li element-containing compound is at least one of an Li element-containing oxide, an Li element-containing nitrate, an Li element-containing sulfate, an Li element-containing carbonate, and an Li element-containing chloride, the Cu element-containing compound is at least one of an Cu element-containing oxide, an Cu element-containing nitrate, an Cu element-containing sulfate, an Cu element-containing carbonate, and an Cu element-containing chloride, and the Ti element-containing compound is at least one of an Ti element-containing oxide, an Ti element-containing nitrate, an Ti element-containing sulfate, an Ti element-containing carbonate, and an Ti element-containing chloride. Specifically, the Na element-containing compound may be at least one of sodium carbonate, sodium hydroxide, and sodium hydrogen carbonate, but is not limited thereto. When mixing, a Na element-containing compound, an M element-containing compound, a Li element-containing compound, a Cu element-containing compound and a Ti element-containing compound can be mixed and mechanically milled to obtain a mixture, and the mechanical milling speed can be, but is not limited to, 100 rpm to 1000 rpm, and the mechanical milling time can be, but is not limited to, 1 hour to 48 hours.

[0038] The amounts of the Na element-containing compound, the M element-containing compound, the Li element-containing compound, the Cu element-containing compound and the Ti element-containing compound can be adjusted based on the theoretical amounts calculated according to the atomic ratios of the Na element, the M element, the Li element, the Cu element and the Ti element, and the theoretical amounts can be expressed by the following formulas: Theoretical amount of Na-containing compound = (α) x (molecular weight of Na-containing compound) x arbitrary constant / (number of Na atoms per Na-containing compound) Theoretical amount of M element-containing compound = (a) x (molecular weight of M element-containing compound) x arbitrary constant / (number of M element atoms per M element-containing compound) Theoretical amount of Li-containing compound = (b) x (molecular weight of Li-containing compound) x arbitrary constant / (number of Li atoms per Li-containing compound) Theoretical amount of Cu-containing compound = (c) x (molecular weight of Cu-containing compound) x arbitrary constant / (number of Cu atoms per Cu-containing compound) Theoretical amount of Ti-containing compound = (d) x (molecular weight of Ti-containing compound) x arbitrary constant / (number of Ti atoms per Ti-containing compound) Among them, all the arbitrary constants are the same.

[0039] The weighed amounts of the Na element-containing compound, M element-containing compound, Li element-containing compound, Cu element-containing compound and Ti element-containing compound may be 100% to 110% of the theoretical amount, but are not limited thereto, and are preferably 102% to 106%, more preferably 103%. In a preferred example, the weighed amounts of the M element-containing compound, Cu element-containing compound and Ti element-containing compound may be 100% of the theoretical amount, and the weighed amounts of the Na element-containing compound and Li element-containing compound may be 100% to 110% of the theoretical amount, preferably 102% to 106%, more preferably 103%.

[0040] The mixture is then fired to obtain a sodium ion positive electrode material by co-doping with multiple elements. Specifically, the firing temperature may be, but is not limited to, 700°C to 1050°C, the firing time may be, but is not limited to, 6 hours to 36 hours, and the heating rate may be, but is not limited to, 1°C / min to 20°C / min. In order to obtain a suitable particle size of the positive electrode material, the material may be further cooled after firing, crushed, and sieved through a 300 mesh screen.

[0041] The third embodiment of the present invention proposes a method for preparing a multi-element co-doped sodium ion positive electrode material, and the multi-element co-doped sodium ion positive electrode material is as described above, so the description is omitted here. This method is a co-precipitation method, and the detailed steps are as follows: First, the chemical formula MCO 3 or M(OH) 2 According to the atomic ratio of M element in the above, an appropriate amount of M element-containing nitrate or M element-containing sulfate is weighed out and dissolved in water, and the pH is adjusted with a precipitant and a complexing agent to uniformly precipitate the precursor MCO. 3 or M(OH) 2 Specifically, the pH adjusted by the precipitant and complexing agent may be, but is not limited to, 7.5 to 13, examples of the precipitant may be, but is not limited to, sodium hydroxide or sodium carbonate, examples of the complexing agent may be, but is not limited to, ammonia water, the drying temperature may be, but is not limited to, 80°C to 150°C, and the drying time may be, but is not limited to, 6 hours to 48 hours.

[0042] Next, the chemical formula Na α M a Li b Cu c Ti d O 2+β According to the atomic ratio of Na, M, Li, Cu, and Ti in the Na-containing compound, Li-containing compound, Cu-containing compound, Ti-containing compound, and precursor MCO 3 or M(OH) 2A suitable amount of each of the following is weighed out and mixed to obtain a mixture. Specifically, the Li element-containing compound, the Cu element-containing compound, and the Ti element-containing compound may be at least one of metal oxide, metal nitrate, metal sulfate, metal carbonate, and metal chloride independently, but are not limited thereto. For example, the Li element-containing compound is at least one of Li element-containing oxide, Li element-containing nitrate, Li element-containing sulfate, Li element-containing carbonate, and Li element-containing chloride, the Cu element-containing compound is at least one of Cu element-containing oxide, Cu element-containing nitrate, Cu element-containing sulfate, Cu element-containing carbonate, and Cu element-containing chloride, and the Ti element-containing compound is at least one of Ti element-containing oxide, Ti element-containing nitrate, Ti element-containing sulfate, Ti element-containing carbonate, and Ti element-containing chloride. Specifically, the Na element-containing compound is at least one of sodium carbonate, sodium hydroxide, and sodium hydrogen carbonate. When mixed, the Na element-containing compound, the Li element-containing compound, the Cu element-containing compound, the Ti element-containing compound, and the precursor MCO 3 or M(OH) 2 The mixture can be obtained by mixing and mechanically milling the mixture, the speed of the mechanical milling can be, but is not limited to, 100 rpm to 1000 rpm, and the time of the mechanical milling can be, but is not limited to, 1 hour to 48 hours.

[0043] Na element-containing compound, Li element-containing compound, Cu element-containing compound, Ti element-containing compound, and precursor MCO 3 or M(OH) 2 The weighed amounts of can be adjusted based on the theoretical amounts calculated according to the atomic ratio of Na, M, Li, Cu, and Ti elements, and the theoretical amounts can be expressed by the following formulas: Theoretical amount of Na-containing compound = (α) x (molecular weight of Na-containing compound) x arbitrary constant / (number of Na atoms per Na-containing compound) Theoretical amount of Li-containing compound = (b) x (molecular weight of Li-containing compound) x arbitrary constant / (number of Li atoms per Li-containing compound) Theoretical amount of Cu-containing compound = (c) x (molecular weight of Cu-containing compound) x arbitrary constant / (number of Cu atoms per Cu-containing compound) Theoretical amount of Ti-containing compound = (d) x (molecular weight of Ti-containing compound) x arbitrary constant / (number of Ti atoms per Ti-containing compound) Precursor MCO 3 or M(OH) 2 Theoretical amount of = (a) x (precursor MCO 3 or M(OH) 2 (molecular weight of) x arbitrary constant Among them, all the arbitrary constants are the same.

[0044] Na element-containing compound, Li element-containing compound, Cu element-containing compound, Ti element-containing compound, and precursor MCO 3 or M(OH) 2 The weighed amount of may be 100% to 110% of the theoretical amount, preferably 102% to 106%, more preferably 103%. In a preferred example, the Cu element-containing compound, the Ti element-containing compound and the precursor MCO 3 or M(OH) 2 The weighed amount of the Na element-containing compound and the Li element-containing compound may be 100% to 110% of the theoretical amount, preferably 102% to 106%, and more preferably 103%.

[0045] The mixture is then fired to obtain a sodium ion positive electrode material by co-doping with multiple elements. Specifically, the firing temperature may be, but is not limited to, 700°C to 1050°C, the firing time may be, but is not limited to, 6 hours to 36 hours, and the heating rate may be, but is not limited to, 1°C / min to 20°C / min. In order to obtain a suitable particle size of the positive electrode material, the material may be further cooled after firing, crushed, and sieved through a 300 mesh screen.

[0046] The fourth embodiment of the present invention proposes a sodium ion battery including the multi-element co-doped sodium ion positive electrode material as described above. Specifically, the multi-element co-doped sodium ion positive electrode material can be mixed with an adhesive to form a positive electrode of the battery. Specifically, the adhesive can be at least one of SP and PVDF, but is not limited thereto. In addition, the mass ratio of the multi-element co-doped sodium ion positive electrode material to the adhesive can be, but is not limited thereto, (70-95):(5-30), and is preferably 90:10. Furthermore, the sodium ion battery can be used in, but is not limited to, large-scale energy storage devices of low-speed two-wheelers, electric vehicles, wind power generation, smart grid peak adjustment, solar power generation, home power supply, or communication base station.

[0047] The present invention is illustrated by the following examples: Example 1

[0048] In this embodiment, the positive electrode material NaMn 0.5 Ni 0.25 Li 0.05 Cu 0.1 Ti 0.1 O 2 The preparation and description are as follows: Chemical formula NaMn 0.5 Ni 0.25 Li 0.05 Cu 0.1 Ti 0.1 O 2 According to the stoichiometric ratio, appropriate amounts of sodium carbonate, dimanganese trioxide, nickel oxide, lithium carbonate, copper oxide and titanium dioxide were weighed out, of which the amounts of sodium carbonate and lithium carbonate were 103% of the theoretical addition amounts, and the above raw materials were placed in a ball mill and mechanically milled at a ball mill rotation speed of 350 rpm for 6 hours.

[0049] The mixture after ball milling was placed in a high-temperature furnace and fired at 875°C for 12 hours with a heating rate of 5°C / min. The mixture was then cooled, crushed, and sieved through a 300 mesh sieve to obtain the positive electrode material (shown in Figure 1).

[0050] The positive electrode material prepared above, SP, and PVDF were made into a slurry in a mass ratio of 90:5:5, which was then coated, dried, and cut into a positive electrode. The positive electrode was also assembled into a coin-type battery, and its electrochemical performance was evaluated. Example 2

[0051] In this embodiment, the positive electrode material NaMn 0.5 Ni 0.25 Li 0.05 Cu 0.15 Ti 0.05 O 2 The preparation and description are as follows: Chemical formula NaMn 0.5 Ni 0.25 Li 0.05 Cu 0.15 Ti 0.05 O 2 According to the stoichiometric ratio, appropriate amounts of sodium carbonate, dimanganese trioxide, nickel oxide, lithium carbonate, copper oxide and titanium dioxide were weighed out, of which the amounts of sodium carbonate and lithium carbonate were 103% of the theoretical addition amounts, and the above raw materials were placed in a ball mill and mechanically milled at a ball mill rotation speed of 350 rpm for 6 hours.

[0052] The mixture after ball milling was placed in a high-temperature furnace and fired at 875°C for 12 hours with a heating rate of 5°C / min. The mixture was then cooled, crushed, and sieved through a 300 mesh sieve to obtain a positive electrode material.

[0053] The positive electrode material prepared above, SP, and PVDF were made into a slurry in a mass ratio of 90:5:5, which was then coated, dried, and cut into a positive electrode. The positive electrode was also assembled into a coin-type battery, and its electrochemical performance was evaluated. Example 3

[0054] In this embodiment, the positive electrode material NaMn 0.5 Ni 0.25 Li 0.075 Cu 0.1 Ti 0.075 O 2 The preparation and description are as follows: Chemical formula NaMn 0.5 Ni 0.25 Li 0.075 Cu0.1 Ti 0.075 O 2 According to the stoichiometric ratio, appropriate amounts of sodium carbonate, dimanganese trioxide, nickel oxide, lithium carbonate, copper oxide and titanium dioxide were weighed out, of which the amounts of sodium carbonate and lithium carbonate were 103% of the theoretical addition amounts, and the above raw materials were placed in a ball mill and mechanically milled at a ball mill rotation speed of 350 rpm for 6 hours.

[0055] The mixture after ball milling was placed in a high-temperature furnace and fired at 875°C for 12 hours with a heating rate of 5°C / min. The mixture was then cooled, crushed, and sieved through a 300 mesh sieve to obtain the positive electrode material (shown in Figure 2).

[0056] The positive electrode material prepared above, SP, and PVDF were made into a slurry in a mass ratio of 90:5:5, which was then coated, dried, and cut into a positive electrode. The positive electrode was also assembled into a coin-type battery, and its electrochemical performance was evaluated. Example 4

[0057] In this embodiment, the positive electrode material NaMn 0.5 Ni 0.25 Li 0.075 Cu 0.1 Ti 0.075 O 2 The preparation and description are as follows: Chemical formula Mn 0.667 Ni 0.333 (OH) 2 According to the stoichiometric ratio, appropriate amounts of nickel sulfate and manganese sulfate were weighed out and dissolved in a certain amount of water. The pH was adjusted with sodium hydroxide and ammonia water to cause uniform precipitation. After drying at 100°C, the precursor Mn 0.667 Ni 0.333 (OH) 2 was obtained.

[0058] Chemical formula NaMn 0.5 Ni 0.25 Li 0.075 Cu 0.1 Ti 0.075 O 2According to the stoichiometric ratio, the above precursor, sodium carbonate, lithium carbonate, copper oxide, and titanium dioxide were appropriately weighed out and placed in a mill for mechanical milling at a ball mill speed of 200 rpm for 8 hours to obtain a mixture.

[0059] The mixture after ball milling was placed in a high-temperature furnace and fired at 850°C, the firing time was 15 hours, the heating rate was 5°C / min, and the mixture was cooled, crushed, and sieved through a 300 mesh sieve to obtain a positive electrode material.

[0060] The positive electrode material prepared above, SP, and PVDF were made into a slurry in a mass ratio of 90:5:5, which was then coated, dried, and cut into a positive electrode. The positive electrode was also assembled into a coin-type battery, and its electrochemical performance was evaluated. Example 5

[0061] In this embodiment, the positive electrode material NaMn 0.4 Ni 0.2 Fe 0.15 Li 0.075 Cu 0.1 Ti 0.075 O 2 The preparation and description are as follows: Chemical formula NaMn 0.4 Ni 0.2 Fe 0.15 Li 0.075 Cu 0.1 Ti 0.075 O 2 According to the stoichiometric ratio, appropriate amounts of sodium carbonate, dimanganese trioxide, nickel oxide, diferric oxide, lithium carbonate, copper oxide and titanium dioxide were weighed out, of which the amounts of sodium carbonate and lithium carbonate were 103% of the theoretical addition amounts, and the above raw materials were placed in a ball mill and mechanically milled for 6 hours at a ball mill rotation speed of 350 rpm.

[0062] The mixture after ball milling was placed in a high-temperature furnace and fired at 875°C for 12 hours with a heating rate of 5°C / min. The mixture was then cooled, crushed, and sieved through a 300 mesh sieve to obtain a positive electrode material.

[0063] The positive electrode material prepared above, SP, and PVDF were made into a slurry in a mass ratio of 90:5:5, which was then coated, dried, and cut into a positive electrode. The positive electrode was also assembled into a coin-type battery, and its electrochemical performance was evaluated. Comparative Example 1

[0064] In this comparative example, the positive electrode material NaMn 0.5 Ni 0.25 Li 0.25 O 2 The preparation and description are as follows: Chemical formula NaMn 0.5 Ni 0.25 Li 0.25 O 2 In accordance with the stoichiometric ratio, appropriate amounts of sodium carbonate, dimanganese trioxide, nickel oxide, and lithium carbonate were weighed out, of which the amounts of sodium carbonate and lithium carbonate were 103% of the theoretical amounts. The above raw materials were placed in a ball mill and mechanically milled at a ball mill rotation speed of 350 rpm for 6 hours.

[0065] The mixture after ball milling was placed in a high-temperature furnace and fired at 875°C for 12 hours with a heating rate of 5°C / min. The mixture was then cooled, crushed, and sieved through a 300 mesh sieve to obtain a positive electrode material.

[0066] The positive electrode material prepared above, SP, and PVDF were made into a slurry in a mass ratio of 90:5:5, which was then coated, dried, and cut into a positive electrode. The positive electrode was also assembled into a coin-type battery, and its electrochemical performance was evaluated. Comparative Example 2

[0067] In this comparative example, the positive electrode material NaMn 0.5 Ni 0.25 Cu 0.25 O 2 The preparation and description are as follows: Chemical formula NaMn 0.5 Ni 0.25 Cu 0.25 O 2According to the stoichiometric ratio, appropriate amounts of sodium carbonate, manganese trioxide, nickel oxide, and copper oxide were weighed out, of which the amount of sodium carbonate was 103% of the theoretical amount, and the above raw materials were placed in a ball mill and mechanically milled at a ball mill rotation speed of 350 rpm for 6 hours.

[0068] The mixture after ball milling was placed in a high-temperature furnace and fired at 875°C for 12 hours with a heating rate of 5°C / min. The mixture was then cooled, crushed, and sieved through a 300 mesh sieve to obtain a positive electrode material.

[0069] The positive electrode material prepared above, SP, and PVDF were made into a slurry in a mass ratio of 90:5:5, which was then coated, dried, and cut into a positive electrode. The positive electrode was also assembled into a coin-type battery, and its electrochemical performance was evaluated. Comparative Example 3

[0070] In this comparative example, the positive electrode material NaMn 0.5 Ni 0.25 Ti 0.25 O 2 The preparation and description are as follows: Chemical formula NaMn 0.5 Ni 0.25 Ti 0.25 O 2 According to the stoichiometric ratio, appropriate amounts of sodium carbonate, dimanganese trioxide, nickel oxide, and titanium dioxide were weighed out, of which the amount of sodium carbonate was 103% of the theoretical amount, and the above raw materials were placed in a ball mill and mechanically milled at a ball mill rotation speed of 350 rpm for 6 hours.

[0071] The mixture after ball milling was placed in a high-temperature furnace and fired at 875°C for 12 hours with a heating rate of 5°C / min. The mixture was then cooled, crushed, and sieved through a 300 mesh sieve to obtain a positive electrode material.

[0072] The positive electrode material prepared above, SP, and PVDF were made into a slurry in a mass ratio of 90:5:5, which was then coated, dried, and cut into a positive electrode. The positive electrode was also assembled into a coin-type battery, and its electrochemical performance was evaluated. Comparative Example 4

[0073] In this comparative example, the positive electrode material NaMn 0.5 Ni 0.25 Li 0.125 Cu 0.125 O 2 The preparation and description are as follows: Chemical formula NaMn 0.5 Ni 0.25 Li 0.125 Cu 0.125 O 2 In accordance with the stoichiometric ratio, appropriate amounts of sodium carbonate, dimanganese trioxide, nickel oxide, lithium carbonate, and copper oxide were weighed out, of which the amounts of sodium carbonate and lithium carbonate were 103% of the theoretical amounts. The above raw materials were placed in a ball mill and mechanically milled at a ball mill rotation speed of 350 rpm for 6 hours.

[0074] The mixture after ball milling was placed in a high-temperature furnace and fired at 875°C for 12 hours with a heating rate of 5°C / min. The mixture was then cooled, crushed, and sieved through a 300 mesh sieve to obtain a positive electrode material.

[0075] The positive electrode material prepared above, SP, and PVDF were made into a slurry in a mass ratio of 90:5:5, which was then coated, dried, and cut into a positive electrode. The positive electrode was also assembled into a coin-type battery, and its electrochemical performance was evaluated. Comparative Example 5

[0076] In this comparative example, the positive electrode material NaMn 0.5 Ni 0.25 Li 0.125 Ti 0.125 O 2 The preparation and description are as follows: Chemical formula NaMn 0.5 Ni 0.25 Li 0.125 Ti 0.125 O 2 In accordance with the stoichiometric ratio, appropriate amounts of sodium carbonate, dimanganese trioxide, nickel oxide, lithium carbonate, and titanium dioxide were weighed out, of which the amounts of sodium carbonate and lithium carbonate were 103% of the theoretical amounts. The above raw materials were placed in a ball mill and mechanically milled at a ball mill rotation speed of 350 rpm for 6 hours.

[0077] The mixture after ball milling was placed in a high-temperature furnace and fired at 875°C for 12 hours with a heating rate of 5°C / min. The mixture was then cooled, crushed, and sieved through a 300 mesh sieve to obtain a positive electrode material.

[0078] The positive electrode material prepared above, SP, and PVDF were made into a slurry in a mass ratio of 90:5:5, which was then coated, dried, and cut into a positive electrode. The positive electrode was also assembled into a coin-type battery, and its electrochemical performance was evaluated. Comparative Example 6

[0079] In this comparative example, the positive electrode material NaMn 0.5 Ni 0.25 Cu 0.125 Ti 0.125 O 2 The preparation and description are as follows: Chemical formula NaMn 0.5 Ni 0.25 Cu 0.125 Ti 0.125 O 2 According to the stoichiometric ratio, appropriate amounts of sodium carbonate, dimanganese trioxide, nickel oxide, copper oxide, and titanium dioxide were weighed out, of which the amount of sodium carbonate was 103% of the theoretical amount, and the above raw materials were placed in a ball mill and mechanically milled at a ball mill rotation speed of 350 rpm for 6 hours.

[0080] The mixture after ball milling was placed in a high-temperature furnace and fired at 875°C for 12 hours with a heating rate of 5°C / min. The mixture was then cooled, crushed, and sieved through a 300 mesh sieve to obtain a positive electrode material.

[0081] The positive electrode material prepared above, SP, and PVDF were made into a slurry in a mass ratio of 90:5:5, which was then coated, dried, and cut into a positive electrode. The positive electrode was also assembled into a coin-type battery, and its electrochemical performance was evaluated.

[0082] See Figure 3, and compared with the standard JCPDS 54-0887, it was found that the positive electrode materials obtained in these examples have a space group of R3-m. See Figure 4, and it was found that all of these examples can provide the battery with an immediate charge-discharge effect. See Figure 5, and it was found that these examples provide the battery with high capacity retention even after 100 charge-discharge cycles.

[0083] Please refer to Table 1, Examples 1 to 3 are prepared by almost the same process, and the atomic ratio of Mn element and Ni element of the positive electrode material is the same, so that the appropriate atomic ratio of Li element, Cu element and Ti element of the positive electrode material is obtained. Examples 3 and 5 are prepared by almost the same process, and the atomic ratio of Li element, Cu element and Ti element of the positive electrode material is the same, so that it is found that the performance of the battery is deteriorated when the positive electrode material contains Fe element.

[0084] Please continue to refer to Table 1. Comparative Examples 1 to 3 have almost the same preparation process as that of Example 1, and the atomic ratio of Mn element and Ni element in the positive electrode material is the same. As a result, the performance brought about by the Li element, Cu element and Ti element together in the battery is better than that brought about by any one of the Li element, Cu element and Ti element, which shows that the Li element, Cu element and Ti element can play a synergistic effect on the battery performance.

[0085] Please continue to refer to Table 1. Comparative Examples 4 to 6 are prepared using almost the same process as that of Example 1, and have the same atomic ratio of Mn element and Ni element in the positive electrode material. As a result, the performance brought about by the Li element, Cu element and Ti element together in the battery is better than any two of the Li element, Cu element and Ti element, which shows that the Li element, Cu element and Ti element can play a synergistic effect on the battery performance.

[0086] Table 1. Electrochemical test results JPEG2024546419000002.jpg93170

[0087] The above contents related to common knowledge are not explained in detail and can be understood by those skilled in the art.

[0088] The above description is merely a few specific embodiments of the present invention, and is not intended to limit the present invention, and any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention. The technical scope of the present invention is not limited to the contents of the specification, and should be determined by the claims.

Claims

1. A multi-element co-doped sodium ion positive electrode material, The positive electrode material is in the O3 phase, has a space group of R-3m, and has the chemical formula Na α M a Li b Cu c Ti d O 2+β wherein M is at least one of Ni, Co, Mn, Cr, V, Al, Fe, B, Si, Mg, and Zn; and 0.5≦α≦1, −0.1≦β≦0.1, 0<a<0.95, 0<b<0.25, 0<c<0.3, 0<d<0.6, a+b+c+d=1, and the sodium ion positive electrode material by multi-element co-doping is electrically neutral.

2. 2. The positive electrode material according to claim 1, wherein M is one, two or three of Ni, Mn and Fe.

3. 2. The positive electrode material according to claim 1, wherein 0.05≦a+b+c<1.

4. 2. A method for preparing a positive electrode material according to claim 1, comprising: Chemical formula Na α M a Li b Cu c Ti d O 2+β weighing out appropriate amounts of a Na-element-containing compound, an M-element-containing compound, a Li-element-containing compound, a Cu-element-containing compound and a Ti-element-containing compound according to the atomic ratio of the Na element, the M element, the Li element, the Cu element and the Ti element in the above, and mixing them to obtain a mixture; and calcining the mixture to obtain the multi-element co-doped sodium ion cathode material.

5. The M element-containing compound, the Li element-containing compound, the Cu element-containing compound, and the Ti element-containing compound are independently at least one of a metal oxide, a metal nitrate, a metal sulfate, a metal carbonate, and a metal chloride; and / or 5. The method according to claim 4, wherein the Na element-containing compound is at least one of sodium carbonate, sodium hydroxide, and sodium bicarbonate.

6. The weight amount of the Na element-containing compound is 100% to 110% of the theoretical amount calculated according to the atomic ratio of the Na element, the M element, the Li element, the Cu element, and the Ti element, and / or The preparation method according to claim 4 or 5, characterized in that the weighed amount of the Li element-containing compound is 100% to 110% of the theoretical amount.

7. 5. The method according to claim 4, wherein the mixing step includes mixing the Na element-containing compound, the M element-containing compound, the Li element-containing compound, the Cu element-containing compound and the Ti element-containing compound, and subjecting the mixture to mechanical milling, wherein the speed of mechanical milling is 100 rpm to 1000 rpm, and the time is 1 hour to 48 hours.

8. The preparation method according to claim 4, characterized in that the calcination temperature is 700°C to 1050°C, the calcination time is 6 hours to 36 hours, and the heating rate is 1°C / min to 20°C / min.

9. 2. A method for preparing a positive electrode material according to claim 1, comprising: Chemical formula MCO 3 Or M(OH) 2 According to the atomic ratio of the M element in the above, an appropriate amount of M element-containing nitrate or M element-containing sulfate is weighed out and dissolved in water, and the pH is adjusted with a precipitant and a complexing agent to uniformly precipitate the precursor MCO. 3 Or M(OH) 2 and Chemical formula Na α M a Li b Cu c Ti d O 2+β In accordance with the atomic ratio of Na, M, Li, Cu, and Ti in 3 Or M(OH) 2 and mixing to obtain a mixture; and calcining the mixture to obtain the multi-element co-doped sodium ion cathode material.

10. The Li element-containing compound, the Cu element-containing compound, and the Ti element-containing compound are independently at least one of a metal oxide, a metal nitrate, a metal sulfate, a metal carbonate, and a metal chloride; and / or 10. The method according to claim 9, wherein the Na element-containing compound is at least one of sodium carbonate, sodium hydroxide, and sodium bicarbonate.

11. The weight amount of the Na element-containing compound is 100% to 110% of the theoretical amount calculated according to the atomic ratio of the Na element, the M element, the Li element, the Cu element, and the Ti element, and / or The preparation method according to claim 9 or 10, characterized in that the weight amount of the Li element-containing compound is 100% to 110% of the theoretical amount.

12. 10. The preparation method according to claim 9, wherein the pH of the precursor obtaining step is 7.5-13, the precipitating agent is sodium hydroxide or sodium carbonate, the complexing agent is ammonia water, the drying temperature is 80°C-150°C, and / or the drying time is 6 hours-48 hours.

13. 10. The method of claim 9, wherein the mixing step includes mixing the Na element-containing compound, the M element-containing compound, the Li element-containing compound, the Cu element-containing compound and the Ti element-containing compound, and subjecting the mixture to mechanical milling, wherein the speed of mechanical milling is 100 rpm to 1000 rpm, and the time is 1 hour to 48 hours.

14. The preparation method according to claim 9, characterized in that the calcination temperature is 700°C to 1050°C, the calcination time is 6 hours to 36 hours, and the heating rate is 1°C / min to 20°C / min.

15. A sodium ion battery, comprising the positive electrode material of claim 1.

Citation Information

Patent Citations

  • Positive electrode active material for sodium-ion battery, sodium-ion battery made of same, battery module, battery pack, and device

    CN112670497A

  • High-voltage sodium ion battery layered oxide positive electrode material

    CN113764669A

  • Positive electrode active material, method for manufacturing the same, and secondary battery

    JP2018195581A

  • Positive electrode active material for sodium ion battery, sodium ion battery made from same, battery module, battery pack and apparatus

    US20220123299A1

  • Non-aqueous electrolyte solution for sodium ion secondary battery, and sodium ion secondary battery

    WO2020175638A1